Kajian Model Pembelajaran Problem Based Learning (PBL) dalam Pembelajaran di Sekolah - Selvi Meilasari; Damris M Damris M; Upik Yelianti (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2020)
This study aims to analyze the application of Problem Based Learning (PBL) models in learning in schools. This form of research is literature studies. The method used is descriptive qualitative to analyze the application of Problem Based Learning (PBL) model. Data collection techniques use documentation, by searching journals relevant to Problem Based Learning (PBL) through Sinta and Google Scholar (Google Scholar) with the research journal period of 2015-2020. The keyword used for journal search is the Problem Based Learning (PBL) model. The journals obtained as many as 231 journals were then selected 41 journals that met the criteria for further analysis. Based on the results of analysis from 41 journals that obtained information; 1) Problem Based Learning (PBL) model found in the field of science that is often applied in schools with a percentage of 77% and in the field of mathematics studies with a percentage of 31%; 2) the application of pbl model has a positive effect on learners, (3) the impact of Problem Based Learning model in learning can increase interest in learning, problem solving ability, learning motivation, critical thinking, and learner learning outcomes. In conclusion, problem based learning models based on literature review results have a positive impact in improving students' learning abilities and interests. Keywords: Problem Based Learning (PBL), Learning Models, Literature Studies